Oral Communication in FLE: Between Reading and Speaking - Seghiour, Mounira (El Omda in Linguistics and Discourse Analysis, 2026)
This article aims to investigate the relationship between reading and oral expression in FLE (French as a Foreign Language). To do so, we administered a questionnaire to first-year LMD students at the University of M’sila. The results of our study confirm the inseparable link between reading and oral expression in FLE.